Risk Factors for Anemia among Pregnant Women: a Case-control Study in Banda Aceh, Indonesia - Nelva Riza; Gadis Halizasia; Komala Kartikasari; Ristiani; Ferdi Riansyah (UPT Publikasi Ilmiah Universitas Islam Bandung, 2025)
Anemia in pregnancy remains a significant public health concern in Indonesia and contributes to adverse maternal and neonatal outcomes. Local evidence on context-specific risk factors in Banda Aceh is limited. This study aimed to identify factors associated with anemia among pregnant women in Banda Aceh, Indonesia. An unmatched case-control study was conducted from June to December 2024 across antenatal care facilities in Banda Aceh. A total of 196 pregnant women were enrolled by consecutive sampling, including 98 anemic cases and 98 non-anemic controls. Hemoglobin levels were measured using an EasyTouch hemoglobin meter, and nutritional status was assessed using mid-upper arm circumference (MUAC). Logistic regression analysis was performed to estimate adjusted odds ratios (aORs) with 95% confidence intervals (CIs). Maternal age at risk (<20 or >35 years) was strongly associated with anemia (aOR=6.39, 95% CI=2.78–14.72, p<0.001). High parity (≥3 pregnancies) also increased the likelihood of anemia (aOR=4.62, 95% CI=2.06–10.34; p<0.001), as did third-trimester gestation (aOR=2.72, 95% CI=1.11–4.84, p=0.025). Chronic energy deficiency (CED) showed a significant association in bivariate analysis and remained clinically relevant. In conclusion, maternal age, parity, and late gestational age were independently associated with anemia among pregnant women in Banda Aceh. Strengthening nutritional screening using MUAC, optimizing birth spacing, and enhancing adherence to iron-folic acid supplementation are essential to reduce anemia-related complications in the region.